Potential of Community Based Ecotourism of Bats Population (Megachiroptera) in Soppeng Regency , Indonesia - Slamet Santosa; Eddy Soekendarsi; Munif Said Hasan; Fahruddin Fahruddin; Dody Priosambodo (Hasanuddin University, 2020)
The bats population lives and reproduces on trees in the city center of Soppeng Regency. The study aims to analyze the potential of community based ecotourism development of bats population. The method of study are the objects and ecotourism attractions, community based ecotourism and ecotourism management analyzes. The :all respondents stated that the bats population can be an ecotourism attraction. It's easy to observe wild bats. Ecotourism is an environmentally friendly tourism trip and empowers local communities. Accessibility is easy because the location of ecotourism attractions is only distance of 0.5 km from the bus terminal and public transportation. Amenities, such as hotel, restaurant, post offices, telecommunication networks, banks and souvenir shop are available at tourist sites. The study concludes that the bats population is potential to be developed as a community based ecotourism object in Soppeng RegencyKey Words : Ecotourism, Bats population, Community Based, Soppeng Regency